Servant Leadership: Maintaining Teacher Commitment And Building Community Trust - Latifatus Saleha; Shahzadi Hina (Al-Qalam Institute, 2023)
This study aims to analyze servant leadership: maintaining teacher commitment and building community trust in educational institutions. This research was conducted at the RA Masyitoh V institution located in the Probolinggo area. This research is a qualitative descriptive research type of case study, in this study the formulation of problems that guide research to explore or photograph social situations that will be researched thoroughly, broadly and deeply. Data were collected using interviews, observations and documentation studies. The sources of informants for this research are principals, teachers and parents. Based on research conducted by servant leadership, it has succeeded in fostering higher teacher commitment and shaping the pattern of public trust in educational institutions. The results revealed that servant leadership implemented in RA Masyitoh V in maintaining teacher commitment and building community trust was carried out by; Leader appreciation for teachers, building collaborative teams, maintaining servant leadership commitment. The implication obtained from the results of this research is the stronger commitment of teachers in carrying out the mandate which has an impact on the growth of public trust in educational institutions with a collaborative relationship from all institutional stakeholders both from within and from outside.